Heterogeneous welfare impacts of National Rural Employment Guarantee Scheme: Evidence from Andhra Pradesh, India - Deininger, Klaus; Liu, Yanyan (Elsevier, 2019)
We use a three-round, 4013-household panel from Andhra Pradesh, together with administrative data and village and population census data, to explore the welfare effects of India’s National Rural Employment Guarantee Scheme (NREGS) on direct beneficiaries. NREGS participants in districts that had been exposed to the program for one year only significantly increased protein and energy intake while in districts with two-year exposure, participants were able to accumulate more nonfinancial assets. The benefits are most pronounced for scheduled casts/scheduled tribes and for the poor, in particular female headed households and households with disabilities. We also find that increased income from casual labor is the primary channel through which the effects are realized. We find no evidence that NREGS participation has resulted in higher private investment in land improvement.